Large Titanium-Oxo Clusters as Precursors to Synthesize the Single Crystals of Ti-MOFs - Sun, Yayong; Lu, Dong-Fei; Sun, Yuexin; Gao, Mei-Yan; Zheng, Nan; Gu, Cheng; Wang, Fei; Zhang, Jian (ACS materials letters, 2021)
Titanium(IV)-based metal-organic frameworks (Ti-MOFs) have received significant attention in recent years because of their numerous photocatalytic applications; however, the synthesis of new Ti-MOFs with precise crystal structures is still challenging. Herein, three new Ti-MOFs with single-crystal structures (denoted as FIR-125–FIR-127) are rationally synthesized by employing a large Ti44-oxo cluster as the precursor to assembly with the organic ligand. Big single-crystals can be successfully obtained and structurally determined by single-crystal X-ray diffraction. During the synthesis, the large Ti44-oxo cluster is transferred to small Ti8O8(CO2)16 building units in the Ti-MOF. In addition, FIR-125 exhibit high stability, permanent porosity, and photocatalytic activity. This work provides a new strategy toward the big crystal growth of Ti-MOFs through the slow transformation of large titanium-oxo clusters.